The Impact Of Collaborative Learning On Students’ Writing Ability And Their Motivation In Writing At MTs Negeri 1 Konawe - Daud, Wahyudi; Hanafi, Hilaluddin; Laepe, Ader (Halu Oleo University, 2018)
This study investigated the The Impact of Collaborative Learning on Students’ Writing Ability and Their Motivation in Writing At Mts Negeri 1 Konawe. The researcher employed Quantitative Rearch Method to conduct this study. Two instruments were employed in this study, those are Achievement Test and Motivation Questionnaire. Population of this study is all the seventh grade students of MTS Negeri 1 Konawe comprised of 2 classes, consist of 42 students were taken as the sample of this study. The data was analyzed by using SPSS16 to measure the the impact of collaborative learning on students’ writing ability and their motivation in writing at Mts Negeri 1 Konawe. The result of this study shows that: (1) There is significant difference of collaborative learning on students’ writing ability. (2) There is positif correlation between motivation in learning and the value of writing students.